Dinámicas urbanas, construcción y ejercicio de ciudadanía en el espacio público - Tristan, Venancia (UNIVERSIDAD DE SONORA, 2021)
From the experience of daily urban life, the questioning of the concept of citizenship and its meaning within the contemporary public space arises, a question derived from the way of thinking about citizenship only from its legal recognition and not as a set of social, cultural, and cultural practices. political and economic, as well as legal in the public space. According to what was proposed, the objective of the work was to analyze the urban processes and actors that intervene in the construction and exercise of citizenship in the public space of the current city: the case of Colonia Mitras centro in the city of Monterrey. With a qualitative approach derived from ethnography, as well as information gathering techniques supported by the theories developed by Gehl Institute, it was possible to analyze the social representations of the inhabitants through their actions, expressed in the practices of the public space in relation to citizenship.